EVIDENCE BASED CASED REPORT (EBCR) : PENGARUH IMD TERHADAP KECEPATAN PELEPASAN PLASENTA KALA III (Jurnal Kesehatan Siliwangi, 2022)
Background: Early initiation of breastfeeding (IMD) is to provide an opportunity for newborns to breastfeed on their own for the first hour by placing the baby on the mother’s chest, and ensuring skin to skin contact between mother and baby. The early initiation of breastfeeding process procedurs the hormone oxytocin which can contraction uterus so that the placenta is born faster. Purpose: The aim of this evidence based case report was to determine the effect of the early initiation of breastfeeding process on the rate of placental detachment in third stage. Metode: A search was conducted on the PubMed and Cochrane Library database toidentify relevant article. There are two articles that meet the criteria and are fully accessible for use and critical review. Critical analysis shows that two articles have good validity. Result: Both articles show that there is an effect of early initiation of breastfeeding on placental delivery in third stage. The results of the LATCH score from one articles can be said that there is influence of early initiatin of breastfeeding on the speed of placental separation in third stage. Conclusion: Infant who do early initiation of breastfeeding will help the process of releasing the placenta faster than infant who don’t do early initiation of breastfeeding.